Oceanographic Data of the 42nd Japanese Antarctic Research Expedition from November 2000 to March 2001 - タカハシ, ワタル; コジマ, テツヤ; セオ, ノリツネ; Takahashi, Wataru; Kojima, Tetsuya; Seo, Noritsune (National Institute of Polar Research, 2002)
P(論文) The results of oceanographic observations on board the icebreaker "Shirase" and tidal observations at Syowa Station, Antarctica, are presented in this report. The oceanographic observations were carried out by the summer party of the 42nd Japanese Antarctic Research Expedition (JARE-42) during the austral summer of 2000/2001. The tidal observations were carried out by the winter party of JARE-41 from February 2000 to January 2001. departmental bulletin paper